Menstrual Abnormalities in a Woman with Acth-Dependent Pituitary Macroadenoma Mimicking Polycystic Ovary Syndrome - Chun-Cheng Liao; Shih-Yi Lin; Hsin-Wang Lin; Kuang-Hua Chen; Lan-Hua Chang; Shun-Tien Chen; John Wang (Elsevier, 2006)
Objective: Here, we present a case of ACTH-dependent pituitary macroadenoma (Cushing's disease) resulting in secondary amenorrhea mimicking polycystic ovary syndrome (PCOS). Case Report: A 20-year-old nulligravid woman had been suffering from oligomenorrhea, amenorrhea, and moderate hirsutism since the age of 18 years. She visited a gynecologic clinic where PCOS was impressed according to the clinical manifestation and ultrasound finding. The patient responded to medication in the 1st year, but gradually failed to induce menses. She was advised to visit the endocrinology department for secondary amenorrhea and endocrine survey. Physical examination revealed central obesity, supraclavicle fatpad, abdominal striae, and myopathy of four limbs. Endocrine studies revealed: serum prolactin 21 ng/mL (3.0-20 ng/mL), FSH 5.69 mIU/mL (3.4-10.0 mIU/mL), LH 1.01 mIU/mL (1.1-11.6 mIU/mL), E2 < 20 pg/mL (follicular phase 53-258 pg/mL), ACTH 110 pg/mL (0-46.0 pg/mL), cortisol 26.7 μg/dL at 8 a.m. (5.0-25 μg/dL), cortisol 21.3 μg/dL at 11 p.m. (half of normal morning value). Right pituitary macroadenoma was diagnosed through a series of dexamethasone tests and MRI. The patient received staging surgery including transsphenoidal adenomectomy and right frontotemporal craniotomy. As a result, the patient's physical condition gradually improved, and her menstrual cycle became regular with medication after the operation in the outpatient follow-up. Conclusion: PCOS is a common disease resulting in secondary amenorrhea. However, Cushing's syndrome resulting from pituitary macroadenoma should also be considered. Therefore, a careful history, observation, physical examination, and endocrine studies can differentiate between patients with PCOS and Cushing's disease.